Implementasi Strategi Pembelajaran Think Pair Share dalam Mata Pelajaran Aqidah Akhlak di MTs Ponpes Modern Darul Hikmah TPI Medan - Arlina, Arlina; Aslamiyah Abda Daulay; Ahmad Rondfiakim Harahap; Audiva Azzahra (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to explore the implementation of the Think Pair Share teaching strategy in the subject of Islamic Faith and Morals at MTs PonPes Modern Darul Hikmah TPI Medan. Utilizing a qualitative method with a phenomenological approach, involving observation and textual analysis, this strategy enhances student engagement and their learning outcomes. Structured steps, such as group discussions and problem-solving, demonstrate increased student involvement. Observation reveals shortcomings in the previous approach, specifically the lack of interaction between teachers and students. As a result, implementing this strategy significantly contributes to improving learning outcomes and classroom interactions. The recommendation is to adopt this model for a more interactive learning experience in the future.